Bhutan: the world's most advanced tobacco control nation?. Issue 4 (5th December 2003) - Ugen, S
Abstract : Significant achievements in the area of tobacco control have been made in the kingdom of Bhutan in the Eastern Himalayas, following the initiation of several tobacco control activities